The Strategic Role of Job Satisfaction in Shaping Organizational Commitment: A Literature Review - Cecilia Indah Hapsari; Arief Noviarakhman Zagladi; Elfia Nora (International Forum of Researchers and Lecturers, 2025)
This study examines the strategic role of job satisfaction in shaping organizational commitment in the context of companies by synthesizing empirical evidence published between 2016 and 2025. Although it has been extensively researched, findings related to the consistency and determinants of the relationship between job satisfaction and organizational commitment are still scattered and have not been integrated, thus requiring comprehensive mapping. Therefore, this study aims to identify empirical patterns, conceptual issues, and theoretical foundations that explain how job satisfaction contributes to the formation of organizational commitment. Using the PRISMA based Systematic Literature Review (SLR) method, 35 articles were selected through the stages of identification, screening, quality assessment, and thematic synthesis. The review results show that job satisfaction is consistently a major predictor of organizational commitment in various corporate sectors. These findings are consistent with theories such as Social Exchange Theory, Equity Theory, Herzberg's Two Factor Theory, and Job Demands Resources Model, which explain the cognitive and affective mechanisms of commitment formation. In addition, variables such as work environment, job involvement, work life balance, internal CSR, and HR practices were identified as mediators or moderators that strengthen this relationship. This study concludes that increasing job satisfaction is an important strategy for strengthening commitment, reducing turnover intentions, and improving organizational performance. This review contributes to an integrative understanding of empirical developments and theoretical perspectives, and provides recommendations for future research to expand the data base and consider cross-cultural dynamics in organizations.